Quality assurance of project management information system with ISO 9126 - Sanjaya, Hadi; Andry, Johanes Fernandes (Bulletin of Social Informatics Theory and Application, 2021)
Information systems are a combination of information technology and the users' activities to support operations and management.  Companies need information systems to improve their business processes. Companies do not want to be left behind by their competitors. One of them is a property developer, where companies need a project management information system. Hope after the creation of this information system will make the company can run the transaction process step by step. With the use of the application compared to the manual, the application can assist companies in carrying out the process in a structured manner and makes it easier for companies to know the profit/loss of a project, and certainly helps companies make reports easier. Making an application must be perfect; there are no errors or bugs. Therefore, this study uses ISO 9126 and sub characteristics to implement and evaluate applications. There are six characteristics of software quality measurement in ISO 9126, namely functionality, efficiency, portability, usability, maintainability, and reliability. This paper only focuses on functionality. 4 types will be discussed in functionality: suitability, accuracy, interoperability, and security.